Sikap masyarakat Gunungkidul terhadap perilaku bunuh diri ditinjau dari jenis kelamin dan tingkat pendidikan - Indriyati Eko Purwaningsih; Ryan Sugiarto; Sulistyo Budiarto (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2022)
Mental health activists believe that the suicides that often occur in Gununkidul are caused by depression as a result of various problems in their lives.The aim of this research is to describe the attitude of the society regarding this phenomenon, in relation to gender and educational status. The subject of this research is the community in Karang Rejek Village, Wonosari District, Gunungkidul. The measuring instrument used is the SPAS Attitude scale. The data was filled in by the subject at the time of the group discussion. Data analysis was carried out by quantitative descriptive, t-test, and product moment correlation. The results of the study concluded that the majority of people have a positive attitude, believe that suicide can be prevented, have good self-control, can assess feelings about the stigma of suicide, can understand and are not affected by stigma against survivors and their families, have empathy and good social relations. and does not differentiate family status and education level. The results of the independent sample test obtained the value of tA1-A2 = -2.317; df = 101; p= 0.023; p < 0.05 significant, so, the hypothesis is accepted. Women have a more positive attitude (mean : 5.748) than men (mean = 5.4890). The second hypothesis test obtained the correlation coefficient of rxy = -0.037; p = 0.357, p > 0.037, so the hypothesis is rejected.